The Effect of Energy and Protein Balance Ration to the Garut Ewes’ Growth - Pri Riznaya; Ana Rochana; Diding Latipudin; Iman Hernaman (Universitas Tidar, 2019)
The purpose of this research was to determine the effect of energy and protein balances on the growth of Garut ewes. The variables are daily consumption, daily weight gain, and conversion ratio value. The treatments given included R1 (12% protein and 60% TDN), R2 (12% protein and 65% TDN), R3 (14% protein and 60% TDN), R4 (14% protein and 65% TDN), R5 (16% protein and 60% TDN), and R6 (16% protein and 65% TDN). The feed is arrange using field grass, fine bran, onggok, soy sauce pulp, coconut cake, and premix. The design of the room uses a Completely Randomized Design (CRD), with 4 (four) replications. Data analysis used variance analysis and Duncan's multiple analysis. The results showed that various protein and energy ratio had a significant effect on daily consumption (whereas R1, R3, and R5 gave better results), but did not affect the daily weight gain and feed conversion ratio value. R6 is the best treatment because it is efficient in consumption and optimal in PBBH and ration conversion value.